Genocide : a reader - Meierhenrich, Jens (New York, NY : Oxford University Press, 2014)
Genocide confounds scholars, practitioners, and laypersons alike. Despite the carnage of the twentieth century, our understanding of genocide remains partial. Popular, moralizing accounts have done their share to hinder understanding by attempting to advance simple truths in an area where none are to be had.
Contents note continued: From UN General Assembly, 60th Session. Draft Resolution Referred to the High-Level Plenary Meeting of the General Assembly by the General Assembly at Its Fifty-ninth Session (A/60/L.1), September 20, 2005.
Includes bibliographical references and index.
Keywords: Genocide; Genocide